2015
DOI: 10.1158/1535-7163.mct-14-0337
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Multitargeted Kinase Inhibitors and Nucleoside Drugs: Achilles Heel of Combination Therapy?

Abstract: Multitargeted tyrosine kinase inhibitors (TKI) axitinib, pazopanib, and sunitinib are used to treat many solid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We found that at the doses administered, ponatinib did not enhance the effect of this combination therapy in vivo . The absence of synergy of ponatinib with gemcitabine and cisplatin may be due to the relatively high dose of gemcitabine and cisplatin we administered; or alternatively, could be due to the recently demonstrated ability of many tyrosine kinase inhibitors to block accumulation of co-administered gemcitabine in cancer cells, rendering the combination less effective [36]. As the combination of gemcitabine (50 mg/kg) and cisplatin (2.5 mg/kg) almost completely inhibited tumor growth, it was difficult to achieve an additional effect by combination with ponatinib.…”
Section: Discussionmentioning
confidence: 99%
“…We found that at the doses administered, ponatinib did not enhance the effect of this combination therapy in vivo . The absence of synergy of ponatinib with gemcitabine and cisplatin may be due to the relatively high dose of gemcitabine and cisplatin we administered; or alternatively, could be due to the recently demonstrated ability of many tyrosine kinase inhibitors to block accumulation of co-administered gemcitabine in cancer cells, rendering the combination less effective [36]. As the combination of gemcitabine (50 mg/kg) and cisplatin (2.5 mg/kg) almost completely inhibited tumor growth, it was difficult to achieve an additional effect by combination with ponatinib.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical regimen of PTX/Gem combination approved for the first-line treatment of metastatic pancreatic cancer recommends sequential administration of PTX followed by Gem [120]. In some cases, simultaneous delivery or reverse-order delivery may induce additive or even antagonistic effects [121–123]. Moreover, there have been clinical cases where simultaneous chemotherapy combination causes greater toxicity than sequentially-administered drugs with no significant advantages in overall survival time [124].…”
Section: Sequential Deliverymentioning
confidence: 99%
“…For this reason, ENT1 has been postulated to be an emergent transporter of clinical importance, that has to be studied during the development of new molecular entities with nucleoside-like structures according to the International Transporter Consortium [ 15 ]. In this context, it is noteworthy that various tyrosine kinase inhibitors (TKIs), such as the bcr-abl inhibitors nilotinib, ponatinib, bosutinib, dasatinib, and imatinib, the EGF receptor inhibitors erlotinib and gefitinib, and the multi-kinase inhibitors axitinib, pazopanib, sunitinib, and vandetanib, have been shown to inhibit ENT1 activity in vitro [ 16 – 19 ]. Whether other TKIs can also behave as inhibitors for ENT1 is, however, unknown, but likely deserves interest owing to the current development of TKIs as a leading pharmacological class for various therapeutic indications, and to the potential co-administration of nucleoside analogues and TKIs, notably for the treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%